Trends in sleeping difficulty among adolescents in five Nordic countries 2002–2014 - Thorsteinsson, Einar Baldvin; Potrebny, Thomas; Arnarsson, Ársaell Már; Tynjälä, Jorma; Välimaa, Raili; Eriksson, Charli (Nordisk välfärdsforskning | Nordic Welfare Research, 2019)
Sleep has been found to be an important factor in adolescents’ mental and physical health. The aim of the present study was to examine trends in sleep difficulty (i.e., difficulty falling asleep more often than once a week) in the Nordic countries among 11- to 15-year-olds. We analysed Nordic data from the Health Behaviour in School-aged Children study (HBSC), which is conducted every four years, looking specifically at trends in sleep difficulty over a 12-year period from 2002 to 2014. The participants were aged 11 to 15 years. The total number of participants across these years was 113,447. A large percentage (17% to 31% in 2014) of adolescents in the Nordic countries experience sleep difficulty, and these difficulties increased from 2002 to 2014 in Denmark, Finland, Iceland, and Sweden. Only in Norway was there a decrease, mainly due to a reduction in sleep difficulty among 11-year-old boys and girls from 2010 to 2014. Sleep difficulty among boys and girls are prevalent and generally on the rise in the Nordic countries with the exception of Norway. peerReviewed